Translocal Livelihoods, Socio-Economic Differentiation and Lower Level Urbanisation in Uganda - Andersson, Agnes; Mackay, Heather; Mukwaya, Paul Isolo (Wiley Periodicals Inc, 2025)
ABSTRACT In sub‐Saharan Africa, more than a quarter of the urban population lives in small towns, with rapid lower level urbanisation being driven largely by lacking rural opportunities. A growing interest in translocality considers relationships that position livelihoods within multiple spatial contexts. Terms of inclusion in translocal relationships vary, and the socio‐economic differentiation emerging out of these relationships is understudied. We use a mixed‐methods approach, combining survey data with qualitative data collected in seven small towns in Uganda to shed light on their translocal livelihood dynamics and to elucidate the empirical and theoretical linkages between translocality and socio‐economic differentiation.